Community‐led transformation principles: Transforming public health learning systems by centering authentic collaboration with community‐based organizations - Reba Meigs; Amina Sheik Mohamed; Adriana Bearse; Sarah Vicente; Nghi Dang; Asmaa Deiranieh; Reem Zubaidi; Valerie Nash; Maliha Ali; Trenita Childers; Mohammad Wahdatyar; Emily Treichler; et al. (Wiley, 2024)
Abstract Introduction In the face of evolving public health challenges, including emerging diseases, pervasive health disparities, and escalating environmental threats, the integration of learning health system (LHS) principles emerges as a vital strategy for enhancing the adaptability and efficacy of public health initiatives. Traditional approaches within these systems often overlook the potential to deeply involve community‐based organizations (CBO) that are led and staffed by the communities they serve as equal and essential partners in the public health discourse. Methods This commentary proposes a suite of nine community‐led transformation (CLT) principles aimed at reimagining LHS frameworks to authentically incorporate CBOs at their core. Drawing on the experiences from initiatives supporting Afghan refugees, we illustrate the application of these principles through two detailed case studies. Results These examples demonstrate the CLT principles in action and spotlight the enhanced cultural competency, effectiveness, and equitable power distribution that arise from such partnerships. Centering small to mid‐sized CBOs including ethnic‐led and/or faith based within LHS structures enables the system to access invaluable cultural insights, strengthen community bonds, and empower those communities to spearhead their transformative journey toward sustainable health, equity, and well‐being improvements. Conclusion The CLT principles herald a shift toward a more inclusive and co‐led public health paradigm by offering a blueprint for stakeholders eager to forge strong, trust‐based coalitions and cocreate initiatives with community leaders including Black, Indigenous, and People of Color (BIPOC) leaders from ethnic‐led and/or faith‐based CBOs. By embracing these principles, public health systems can evolve into truly inclusive, responsive, and sustainable entities poised to advance health equity for all community members.